A novel, microfluidic high-throughput single-cell encapsulation of human bone marrow mesenchymal stromal cells - Narjes Rashidi; Alex Slater; Giordana Peregrino; Matteo Santin (Journal of Materials Science: Materials in Medicine)
Abstract The efficacy of stem-cell therapy depends on the ability of the transplanted cells to escape early immunological reactions and to be retained at the site of transplantation. The use of tissue engineering scaffolds or injectable biomaterials as carriers has been proposed, but they still present limitations linked to a reliable manufacturing process, surgical practice and clinical outcomes. Alginate microbeads are potential candidates for the encapsulation of mesenchymal stromal cells with the aim of providing a delivery carrier suitable for minimally-invasive and scaffold-free transplantation, tissue-adhesive properties and protection from the immune response. However, the formation of stable microbeads relies on the cross-linking of alginate with divalent calcium ions at concentrations that are toxic for the cells, making control over the beads’ size and a single-cell encapsulation unreliable. The present work demonstrates the efficiency of an innovative, high throughput, and reproducible microfluidic system to produce single-cell, calcium-free alginate coatings of human mesenchymal stromal cells. Among the various conditions tested, visible light and confocal microscopy following staining of the cell nuclei by DAPI showed that the microfluidic system yielded an optimal single-cell encapsulation of 2000 cells/min in 2% w/v alginate microcapsules of reproducible morphology and an average size of 28.2 ± 3.7 µm. The adhesive properties of the alginate microcapsules, the viability of the encapsulated cells and their ability to escape the alginate microcapsule were demonstrated by the relatively rapid adherence of the beads onto tissue culture plastic and the cells’ ability to gradually disrupt the microcapsule shell after 24 h and proliferate. To mimic the early inflammatory response upon transplantation, the encapsulated cells were exposed to proliferating macrophages at different cell seeding densities for up to 2 days and the protection effect of the microcapsule on the cells assessed by time-lapse microscopy showing a shielding effect for up to 48 h. This work underscores the potential of microfluidic systems to precisely encapsulate cells by good manufacturing practice standards while favouring cell retention on substrates, viability and proliferation upon transplantation. Graphical Abstract